Correlation between Clinical Diagnosis and Histological Confirmation of Acute Appendicitis - Ahmad Raza Nasar, Najam-Ud-Din, Abdul Rasheed Zai, Saima Gulzar, Javed Ahmed Memon, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Acute appendicitis is among the most frequent causes of acute abdominal pain and remains a common indication for emergency surgery. While diagnosis is primarily clinical in many settings, histopathological examination remains the gold standard for confirmation. Objective: To determine the frequency of histologically confirmed acute appendicitis among patients who underwent appendectomy based on clinical suspicion alone. Methodology: This descriptive cross-sectional study conducted at Department of General Surgery, University College of Medicine & Dentistry University of Lahore from 1st April 2023 to 30th September 2023. Sixty patients confirmed on histopathological of acute appendicitis were included with non-probability consecutive sampling was used. The sample size was calculated with 95% confidence level Z=1.96, an expected proportion of 80% and 10% margin of error. All patients of either gender, age between 10-60 years presenting with clinical features suggestive of acute appendicitis, underwent emergency appendectomy based solely on clinical diagnosis and provided informed consent for participation were included. Clinical diagnosis was made by the attending surgical team based on history (e.g. pain in right iliac fossa, nausea, vomiting), physical examination (e.g. tenderness at McBurney’s point, rebound tenderness), and supporting laboratory tests (e.g. leukocytosis). Imaging (ultrasound or CT) was used only selectively, primarily in atypical or complicated cases. Data were entered and analyzed using SPSS-26. Results: The mean age of patients was 27.6±9.3 years. Among the 60 patients, 36 (60%) were male and 24 (40%) were female. Histopathological examination confirmed acute appendicitis in 51 patients (85.0%), while 9 patients (15.0%) had a normal appendix, indicating negative appendectomy. Acute suppurative appendicitis was the most common histological subtype (63.3%), followed by gangrenous (15.0%) and perforated appendicitis (6.7%). The negative appendectomy rate was higher among female patients compared to males (20.8% vs. 11.1%). Conclusion: A significant majority of clinical diagnoses of acute appendicitis were histologically confirmed. However, a 15% negative appendectomy rate underscores the limitations of clinical assessment alone. Keywords: Acute appendicitis, Histopathology, Clinical diagnosis, Appendectomy, Negative appendectomy